Immune response of the long-tailed field mouse (Apodemus sylvaticus) to tick-borne encephalitis virus infection - Kopecký, J; Tomková, E; Vlcek, M (Folia parasitologica, 1991)
The immune response following infection with a virulent strain of Central European encephalitis (CEE) virus in a natural host, long-tailed field mouse (Apodemus sylvaticus L.) and white laboratory-bread ICR mouse, was compared. Viraemia was demonstrated in ICR mice after intraperitoneal infection with a dose of 10(5) LD50/0.5 ml. The virus titres were high in the spleen and, particularly, in the brain. In A. sylvaticus the virus was detected in the blood and spleen, but not in the brain. CEE virus multiplied in peritoneal macrophages from ICR mice, but not from A. sylvaticus. The infection induced a strong interferon response in both hosts. The natural killer (NK) cell activity increase was twice as high in A. sylvaticus compared to ICR mice. The neutralization antibodies appeared sooner in A. sylvaticus and reached higher titres in the early phases of infection.
Keywords: Male; protilátky virové; slezina; replikace viru; Brain; Encephalitis Viruses, Tick-Borne; Disease Susceptibility; mužské pohlaví; nemoci hlodavců; Muridae; Spleen; Encephalitis, Tick-Borne; interferony; kultivované buňky; Animals; buněčná imunita; Viremia; ženské pohlaví; Virus Replication; Interferons; zvířata; klíšťová encefalitida; buňky NK; makrofágy; Immunity, Cellular; mozek; myši; Rodent Diseases; Antibodies, Viral; viry klíšťové encefalitidy; Cells, Cultured; viremie; Mice; náchylnost k nemoci; Female; Killer Cells, Natural; Macrophages